A Novel Element Upstream of the Vγ2 Gene in the Murine T Cell Receptor γ Locus Cooperates with the 3′ Enhancer to Act as a Locus Control Region - Baker, Jeanne E. (The Rockefeller University Press, 1999)
Transgenic expression constructs were employed to identify a cis-acting transcription element in the T cell receptor (TCR)-γ locus, called HsA, between the Vγ5 and Vγ2 genes. In constructs lacking the previously defined enhancer (3′E(Cγ1)), HsA supports transcription in mature but not immature T cells in a largely position-independent fashion. 3′E(Cγ1), without HsA, supports transcription in immature and mature T cells but is subject to severe position effects. Together, the two elements support expression in immature and mature T cells in a copy number–dependent, position-independent fashion. Furthermore, HsA was necessary for consistent rearrangement of transgenic recombination substrates. These data suggest that HsA provides chromatin-opening activity and, together with 3′E(Cγ1), constitutes a T cell–specific locus control region for the TCR-γ locus.